ANALISIS MANAJEMEN INDUSTRI HALAL PERSPEKTIF EKONOMI ISLAM - Hida, Fetyh Tanala; Basalamah, Ridwan; Nurhidayati, Nurhidayati (Universitas Al-Amien Prenduan, 2021)
The purpose of this paper is to find out the analysis of halal industry management from the perspective of Islamic Economics. The results of the study stated that the management of the halal industry must consist of halal ingredients, both substances, methods of obtaining and processing. The management of the halal industry must be carried out in the halal industrial area, where all industrial plots must be allocated for halal products, have halal facilities and infrastructure, and have a halal management team. The management of the halal industry is in accordance with the principles and theories of Islamic economics. Where all the principles and theories in Islamic economics are based on the Qur'an and the Hadith of the Prophet.